2022
DOI: 10.1007/s00405-022-07681-4
|View full text |Cite
|
Sign up to set email alerts
|

Volumetry improves the assessment of the vestibular aqueduct size in inner ear malformation

Abstract: Objectives Enlarged vestibular aqueduct (EVA) is a common finding associated with inner ear malformations (IEM). However, uniform radiologic definitions for EVA are missing and various 2D-measurement methods to define EVA have been reported. This study evaluates VA volume in different types of IEM and compares 3D-reconstructed VA volume to 2D-measurements. Methods A total of 98 high-resolution CT (HRCT) data sets from temporal bones were analyzed (56 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…For linear measurements of the VA, the Cincinnati protocol was followed ( 90 ). On the other hand, following the recommendations of Weiss et al ( 91 ), the volume of the VA was measured, establishing its limits at the intersection of this structure with the vestibule and in the plane perpendicular to the opercular rim.…”
Section: Methodsmentioning
confidence: 99%
“…For linear measurements of the VA, the Cincinnati protocol was followed ( 90 ). On the other hand, following the recommendations of Weiss et al ( 91 ), the volume of the VA was measured, establishing its limits at the intersection of this structure with the vestibule and in the plane perpendicular to the opercular rim.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research has found that LVAS can be better diagnosed by measuring the 3D volume of VA (Boston et al, 2007;Weiss et al, 2022). In this study, LVAS was diagnosed by measuring the width of the VA operculum and midpoint.…”
Section: The Rationality Of the Modelmentioning
confidence: 95%